THE INFLUENCE OF STUDENTS' PERCEPTION OF THE QUALITY OF OBJECTIVE TESTS ON THE ACHIEVEMENT OF INDONESIAN LANGUAGE LEARNING OUTCOMES - Sagung Manik Puspa Putri; Ida Bagus Putrayasa; Luh Putu Yudha Budiarti; I Gusti Ayu Diantari Pradnya Dewi; Ni Putu Ayu Widiastiti (SOSIOEDUKASI, 2026)
Quality education always relies on the effectiveness of learning and the accuracy of evaluation. This study aims to empirically examine the contribution of students' perception of the quality of objective tests to the achievement of their Indonesian language learning outcomes. The approach used was quantitative non-experimental with associative/causal Ex Post Facto design of 60 respondents (N = 60). Data were collected using a Likert scale closed-ended questionnaire for test quality perception variables (construction dimensions, substance, and psychometric) as well as objective test pure values for learning outcome variables. The results of the prerequisite test showed that the data were normally distributed and linear (p = 0.792 > 0.05). Furthermore, the hypothesis test using Pearson Product Moment correlation yielded a correlation coefficient value of r = 0.949 with a significance value of 0.000 < 0.01. These results prove that there is a very strong and significant positive relationship between students' perceptions of test quality and their learning outcomes. Thus, students' mental representation of evaluation tools is a crucial factor that determines their academic performance. The implication of this study emphasizes that teachers not only need to pursue the empirical validity of the questions, but also must ensure that evaluation instruments are designed fairly, clearly, and free from ambiguity in order to minimize the external cognitive burden of students.